Effect of intrauterine cocaine exposure on respiratory distress syndrome in very low birthweight infants. - Beeram, M. R. (National Medical Association, 1994)
To evaluate the effect of intrauterine cocaine exposure on lung maturity of very low birthweight infants, the medical records of all infants with birthweight < 1500 g born between January 1989 and December 1990 at DC General Hospital were reviewed. Infants with conditions known to cause lung maturity, severe congenital anomalies, proven early sepsis, and birthweight > or = 500 g were excluded. A total of 69 infants were included in the study. Chest roentgenograms of these infants were evaluated by a pediatric radiologist, who was unaware of the infant's medical course, for evidence of respiratory distress syndrome (RDS), and radiological findings were correlated with clinical signs. Forty infants were exposed to cocaine in utero (cocaine group) and 29 were not exposed (noncocaine group). African-American ethnicity, pregnancy-induced hypertension, prolonged rupture of membranes, and alcohol use were similar in both groups. Tobacco use among cocaine group mothers was higher (42.5% versus 13.8%; P = .01). Gestational age (28.3 +/- 2.8 versus 28.3 +/- 3 weeks), birthweight (966 +/- 282 versus 1059 +/- 295 g), male gender, and Apgar scores were similar in both groups. Thirty (75%) infants in the cocaine group developed RDS compared with 19 (66%) in the noncocaine group (P > .05). Using multiple logistic regression analysis and controlling for smoking, alcohol use, and prolonged rupture of membranes (24 to 72 hours), the incidence of RDS between the groups remained statistically insignificant. We conclude that intrauterine cocaine exposure does not alter the incidence of RDS in very low birthweight infants.